Percutaneous paravertebral endoscopic decompression for the treatment of far-out syndrome involving the L5 nerve root: technical report and preliminary results - Yang, Fei; Feng, Chaoqun; Li, Ke; Fan, Xiaohong; Chen, Rigao (BMC musculoskeletal disorders, 2025)
The aim of this study was to describe the technique of percutaneous paravertebral endoscopic decompression for the treatment of far-out syndrome and to analyze the early clinical results of this technique. From April 2021 to June 2023, a retrospective study was conducted on patients with far-out syndrome who underwent percutaneous paravertebral endoscopic decompression at Hospital of Chengdu University of Traditional Chinese Medicine. The Visual Analogue Scale (VAS), Oswestry Disability Index (ODI), and modified MacNab criteria were utilized for the assessment of leg pain, quality of life, and clinical efficacy, respectively. Clinical outcomes were assessed at the day before surgery, 1 day, 1 month, 3 months, 6 months after surgery, and the last follow-up. Meanwhile, the incidence rate of foraminal stenosis, surgery time, and complications were recorded for comprehensive evaluation. This study included a cohort of 16 patients, with a mean age at the time of surgery of 70.94 ± 4.04 years. The average duration of symptoms was 10.81 ± 5.13 months, while the mean follow-up period lasted for 16.69 ± 5.84 months. The results revealed significant improvements in VAS scores and ODI scores at each time point following the operation (P < 0.05). According to the modified MacNab criteria, excellent or good outcomes were observed in 15 cases (93.70%). Four patients presented with postoperative numbness, which was effectively alleviated through conservative treatment. One case with a fair outcome exhibited residual radicular symptoms. The current technical report presents a successful treatment strategy for far-out syndrome, demonstrating promising preliminary efficacy and safety.